Teleworking: the challenge of work in the post-pandemic world - Schneider, Patrick Verfe; Sugahara, Cibele Roberta; Silva, Luiz Henrique Vieira da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Since 2019, humanity has been affected by one of the most serious pandemics in recent history, caused by the severe acute respiratory syndrome virus 2 (SARS-CoV-2). The number of cases and deaths scalation in Brazil and the significant socioeconomic challenges have led organizations around the globe to recommend isolation and social distance, to mitigate the pandemic impacts. In this context, organizations are looking for alternatives to the temporary interruption of business activities through teleworking. As it proves to be temporary, it begins to take on perpetuity contours, with companies announcing the sale of buildings and the extinction of their offices. The study identified whether initiatives presented elements of precariousness in the work relationship. To this end, the theoretical framework addressed the situation of work relations with the pandemic from the home office. The research method was based on a descriptive study with a qualitative approach and bibliographic design. The discussion showed that, after twelve months since the first confirmed case of Covid-19 in Brazil, it is necessary to regulate teleworking activities, with formalization by means of a contractual amendment, as well as checking if there is any expenditure of extraordinary resources by employees due to the new type of work. It was concluded that all world leaders should be engaged in combating precarious work and this extends to the context of the pandemic, to prevent the atypical modality from facilitating the loosening of labor relations